(untitled) (International Journal of Engineering and Computer Science, 2017)
In general, the structure in high seismic areas may be susceptible to the severe damage due to gravity load and seismic load. The columns and beams are used to transfer the major portion of the gravity loads and some part of lateral loads to the earth. This transfer of loads is not applicable during earthquake. In this project, a research is conducted to check the performance of different bracing system [Steel bracing] for different conditions. For this research G+15 storey RC frame structure 25m x 25 m has been analyzed for 5 days in each direction for seismic zone V. The soil is considered to be as hard soil and soft soil. For this research FE based software ETABS is chosen. Totally 13 models are analyzed for different bracing system with different sections and performance is checked by calculating time period, natural frequency, storey drift and base shear.